Efecto del calentamiento del suelo en la capacidad de sorción de las sustancias húmicas sobre metales y cambios en la repelencia al agua simulando incendios de baja, mediana y alta intensidad en la Reserva Ecológica del Antisana. - Carrera Andrango, Luis Fernando (2017)
Ecuador is a country with diverse ecosystems including the Andean highlands are the same as harboring high biodiversity, besides being considered as a source of stored water. Alterations in these ecosystems have been increasing with the passing of the years mainly by human activities such as deforestation, agriculture, mineral exploitation among others. In recent times a threat that has been gaining strength in these ecosystems are forest fires mostly caused by human hands. In this research the effect of fire on the water repellency of the soil and the sorption capacity (resorption) metals (calcium) is approached, making a fire simulation of different intensities in samples taken from the Ecological Reserve Antisana ( REA). In the process of research physical-chemical parameters such as pH, conductivity, organic matter, organic carbon among others they were also evaluated to determine soil conditions after a fire which also helped to understand the variation of repellency and sorption. It was determined that the reduction of certain parameters such as organic matter influences repellency variation that ranged from the same soil to a very strongly Hydrophobic Hydrophobic Strongly soil samples subjected to the heat treatment of medium and high intensity. With regard to sorption it was identified that there is a slight variation because arrays (soil samples) have greater sorption after heat treatment with a short blunting in the samples to which the heat treatment of high intensity is applied according to the sorption research increases when higher concentration of the metal exists and is what happens with the ground after a fire calcium concentration increases.